763. Correlates of Antiretroviral Therapy Initiation Among Newly Diagnosed Older People with HIV in Ukraine. (31st December 2020) - Allen, Amy J; Zeziulin, Oleksandr; Rozanova, Julia; Litz, Taylor; Zaviryukha, Irina; Postnov, Oleksandr; Kiriazova, Tetiana; Shenoi, Sheela
Abstract: Background: Ukraine has a high burden of HIV, with only 52% of people living with HIV receiving Antiretroviral Therapy (ART) despite test and treat policies and free medications. An underrecognized but significantly increasing proportion of older people with HIV (OPWH) contribute 15% of new HIV diagnoses and demonstrate increased mortality compared to the age-matched general population. To assess the impact of age on HIV treatment outcomes, we examined correlates of ART initiation among newly diagnosed HIV patients in Ukraine. Methods: A retrospective chart review was conducted of 400 patients newly diagnosed with HIV between July 1, 2017- Dec 1, 2018 in Odessa, Ukraine. OPWH were defined as those ≥50 years old at the time of diagnosis, while ART initiation was defined as prescription and dispensing of medication. Outcomes were censored 6 months from diagnosis. Demographic, clinical characteristics, and ART outcomes were examined and multivariable logistic regression models were used to estimate correlates of ART initiation with adjusted odds ratios at 95% confidence intervals. Results: Of the 400 included patients, 198 (49.5%) were < 50 years old and 202 (50.5%) were ≥ 50 years old at the time of diagnosis. Patients ≥50 years old were more likely to have a lower CD4 count (median 148 (IQR 60-316) vs 295 (IQR 111-478), p=0.001). Correlates of ART initiation included age less than 50 and history of opportunistic infection within 12 months of diagnosis. After controlling for opportunistic infection history, OPWH were 51% less likely to receive ART than those < 50 years old at the time of diagnosis (AOR 0.496, CI 0.301-0.816, p=0.006). Conclusion: OPWH exhibit an ART gap associated with advanced disease at presentation compared to younger individuals newly diagnosed with HIV. This is the first clinical data examining OPWH in Ukraine. Interventions to improve linkage to care for OPWH are urgently needed in a population already at increased risk for HIV related mortality. The results of this study emphasize the need for further studies to examine patient and systemic causes of decreased ART initiation among Ukrainian OPWH. Disclosures: All Authors : No reported disclosures